Hubungan Intensitas Nyeri dengan Produksi ASI Padaibu Post Sectio Caesariadi RSUD Perdagangan Kecamatan Bandar Kabupaten Simalungun Tahun 2022 - Wiwin Indiawati; Deby Cyntia Yun; Latria Simamora (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Sectio caesarea is a solution for handling births with complications, Sectio Caesaria in Indonesia every year deliveries with sectio caesaria are increasing. Surgical procedures such as Sectio Caesaria are actions that cause tension (stress) because this action involves removing the fetus through the abdomen (Laparotomy) which requires an incision into the uterus (Hysterotomy). The aim of this research is to find out the relationship between pain intensity and breast milk production in post-cesarean section mothers at RSUD. Data analysis using univariate, bivariate analysis. The results of this study show that there is a significant relationship between pain intensity and breast milk production in post-cesarean mothers at the Bandarkar Subdistrict, Simalungun District Trade Hospital in 2022. It can be used as a source of information for mothers who are about to give birth and postpartum mothers to know about description of the intensity of pain in mothers post Sectio Caesaria at the Trade Hospital which causes disruption in breast milk production.